El control y su valoración de los inventarios y la repercusión en la rentabilidad de la empresa - Bernabé Guzmán, Tatiana Jacqueline (2015)
This proyect integrator has been developed with the purpose to make detailed procedures on the control of inventories to the Agro-artisanal Tenguel Association, due to the fact that this does not have a proper control of these so-called current assets, so that you get a detailed and updated information that is feasible and reliable before the financial situation of the association. In addition ways of controlling the inventories are the details in the procedures of acqusition, encoding and the taking of physical inventories that allow members of the association have a vision about the control that you can carry in your company by helping to make good decisions based on actual results and correct. The study of this topic it was undertaken by relying on the research in scientific articles and bibliographic reviews corresponding to the control and valuation of inventories and the profitability of the company. Also the methodologies used in this work are the descriptive research and foresight were of great assistance to perform this work. In conclusion it is important that any company controls in a thorough manner their inventories since this affects the profitability of the same, therefore it is recommended to implement the proposal of the detailed procedures that will serve as a guide for the control of same.